2015
DOI: 10.1016/j.canlet.2015.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Antibody mediated therapy targeting CD47 inhibits tumor progression of hepatocellular carcinoma

Abstract: Human hepatocellular carcinoma (HCC) has a high rate of tumor recurrence and metastasis, resulting in shortened survival times. The efficacy of current systemic therapies for HCC is limited. In this study, we used xenograft tumor models to investigate the use of antibodies that block CD47 and inhibit HCC tumor growth. Immunostaining of tumor tissue and HCC cell lines demonstrated CD47 over-expression in HCC as compared to normal hepatocytes. Macrophage phagocytosis of HCC cells was increased after treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 15 publications
6
87
0
Order By: Relevance
“…Currently employed antibody therapeutic methods function via inducing antibody-dependent cellular cytotoxicity (ADCC), breaking pivotal receptor-ligand interactions, or other unknown mechanisms [34]. As described in several reports, CD47-SIRPα interactions constituted the main barrier that restricted antibodymediated killing efficiency of tumor cells [35][36][37][38]. Based on the results, we observed that the interaction of CD47 with SIRPα could be interrupted, at least partly, by CD47siRNA and anti-SIRPα (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Currently employed antibody therapeutic methods function via inducing antibody-dependent cellular cytotoxicity (ADCC), breaking pivotal receptor-ligand interactions, or other unknown mechanisms [34]. As described in several reports, CD47-SIRPα interactions constituted the main barrier that restricted antibodymediated killing efficiency of tumor cells [35][36][37][38]. Based on the results, we observed that the interaction of CD47 with SIRPα could be interrupted, at least partly, by CD47siRNA and anti-SIRPα (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Macrophages can also recognize and phagocytose tumors cells upon down-regulation of CD47, a so-called “don’t eat me”-signal, on the tumor cell surface. However, many tumors up-regulate CD47 as an immune escape mechanism, including HCC (Xiao, et al, 2015). Accordingly, a study found that antibody-mediated blockade of CD47 enhances macrophage killing of HCC tumor cells.…”
Section: Cells Of the Hepatic Tumor Environment And Their Regulatimentioning
confidence: 99%
“…In various xenograft tumor models using NOD-scid-IL2Rgamma null (NSG) mice, use of human CD47-blocking monoclonal antibodies has demonstrated superb efficacy against human acute lymphocytic leukemia, acute myeloid leukemia, leiomyosarcoma, and solid tumors [18, 20, 27, 28, 30, 31]. Most work initially concluded that the therapeutic effects of anti-human CD47 were dependent on the direct killing of the tumor by phagocytes.…”
Section: Introductionmentioning
confidence: 99%